2018
DOI: 10.1039/c8cy01023d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of vanadium phosphorus oxide catalysts promoted by iron-based ionic liquids and their catalytic performance in selective oxidation ofn-butane

Abstract: Catalytic performance of undoped and Fe-doped VPO catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…It is founding that the VPO precursors with IL addition exhibit a smaller relative integral intensity of the (001) and (130) planes than the Blank-PVPO, especially for 1%IL-PVPO and 5%IL-PVPO, which is different with conventional method that the addition of metal dopant will remarkably increase the I (001)/(130) values [27]. This phenomenon indicated that IL is able to adjust the growth behavior of the crystal plane of VPO precursors, the same results were also reported in our previous work [26]. In addition to this, a change in IL addition contents from 1 to 3% was found to show a great increase in I (001)/(130) value for IL-PVPO, whereas when the addition amount was higher than 3%, the I (001)/(130) value of the catalyst displays a slight downward trend.…”
Section: Catalyst Characterizationsupporting
confidence: 60%
See 2 more Smart Citations
“…It is founding that the VPO precursors with IL addition exhibit a smaller relative integral intensity of the (001) and (130) planes than the Blank-PVPO, especially for 1%IL-PVPO and 5%IL-PVPO, which is different with conventional method that the addition of metal dopant will remarkably increase the I (001)/(130) values [27]. This phenomenon indicated that IL is able to adjust the growth behavior of the crystal plane of VPO precursors, the same results were also reported in our previous work [26]. In addition to this, a change in IL addition contents from 1 to 3% was found to show a great increase in I (001)/(130) value for IL-PVPO, whereas when the addition amount was higher than 3%, the I (001)/(130) value of the catalyst displays a slight downward trend.…”
Section: Catalyst Characterizationsupporting
confidence: 60%
“…Extensive researches indicated that addition of metal dopants [7,[11][12][13][14][15][16][17][18][19], organic structural directing agent [20][21][22][23] and surfactant [24] during the preparation of VPO were usually employed as effective strategies to enhance its catalytic performance by modulating the crystal structure, morphology as well as chemical properties of the surface (such as P/V ratio, valence state of V, amounts of lattice oxygen, etc.). Recently, metal-based ionic liquids (ILs) acting as additives and promoters were firstly proposed and applied in the synthesis of VPO catalyst for selective conversion of n-butane in our previous work [25,26], the ILs including iron metal was observed to have largely increased the proportion of active phase (VO) 2 P 2 O 7 and induced a great change in structure morphology of VPO owing to their synergistic action between the metal anions and structureguided cations in ILs, the obtained VPO catalyst exhibited excellent performance with high conversion of n-butane and selectivity of MA. In the light of the enlightenment from ILs, the efforts were further made to employ deep eutectic ILs as structural modifier and crystal induced agent to assist the preparation of VPO and obtained a good catalytic behavior [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loosely flaky plates are observed in PVPO‐60 °C (Figure 1d). The sheets become thicker in PVPO‐90 °C (Figure 1e) and all exhibit typical rosette morphology of VPO precursors [4h,16] . The obtained precursor sheets become thicker and more agglomerated as the temperature of reaction system at the time of H 3 PO 4 adding increases, such as PVPO‐110 °C and PVPO‐135 °C (Figure 1h and 1 f).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, organic promoters such as polyethylene glycol (PEG), [5b,c] poly(acrylic acid‐co‐maleic acid) (PAAMA), [5d] and poly(styrene‐alt‐maleic acid) (PSMA) [5e] were used as structure‐directing agents to enhance the crystallinity of VPO. Recently, our group found ionic liquid [4h,6] and deep eutectic solvents (DES) [7] could not only influence the surface chemical state and redox characteristic of catalyst but also benefit for forming single‐crystal structure on precursor surface. Both metal and organic promoters cannot influence the phase composition and structure of the catalyst significantly, key point still exist in the preparation of VPO precursor which determined the form of the active phase (amorphous versus crystallized) and the nature of the active components [8] .…”
Section: Introductionmentioning
confidence: 99%